2017
DOI: 10.4018/ijskd.2017040101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Web Attributes on Consumer Purchase Intentions

Abstract: The rise in the number of households possessing computers and the ease of internet access has led to widespread acceptance of B2C e-commerce, and has rapidly evolved into a global phenomenon. The competition among e-commerce vendors is getting intensified year by year and all of them are adopting innovative and creative approaches to attract, satisfy and retain customers. Web attributes are considered as one of the key influencers of consumer purchase intentions. With the support of existing literature, an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Previous scholars have suggested that e-retailers initially exert effort to decrease the level of risk, which improves customer trust and ultimately increases purchase intention for buying online products/services. The privacy/security features of websites and shared values are also critical factors of trust in online shopping (Arnott et al, 2007;Katta & Patro, 2017). Therefore, this paper hypothesizes: H4.…”
Section: Trust In Online Shoppingmentioning
confidence: 95%
“…Previous scholars have suggested that e-retailers initially exert effort to decrease the level of risk, which improves customer trust and ultimately increases purchase intention for buying online products/services. The privacy/security features of websites and shared values are also critical factors of trust in online shopping (Arnott et al, 2007;Katta & Patro, 2017). Therefore, this paper hypothesizes: H4.…”
Section: Trust In Online Shoppingmentioning
confidence: 95%
“…Interest Buying is the stage where consumers evaluate the information received (Hasan & Sohail, 2020;Hong & Cho, 2011;Kajtazi & Zeqiri, 2020;Kalia et al, 2016;Katta & Patro, 2017;Pokryshevskaya & Antipov, 2012;Rubab et al, 2018;Tweephoncharoen & Vongurai, 2019) . In this context, a person's willingness to buy has a higher probability, even though they may not actually buy it (Hsu, 2017).…”
Section: Consumer Interest Theory In Choosing -Interest Buyingmentioning
confidence: 99%
“…In contrast to conventional shopping, digital shopping has gained volatile progress as it signifies a more economic and appropriate means of buying. The digital marketplace offers buyers the required information for product comparisons, the opportunity to get competitive prices, a wide range of product selections and easy access to required products (Katta & Patro, 2017a). It also offers a greater shopping experience and consummation to contemporary buyers looking for expediency and speediness in procuring the products (Yu & Wu, 2007;Saha & Mathew, 2021).…”
Section: Introductionmentioning
confidence: 99%